FAULKNERIAN TRADITIONS IN CONTEMPORARY UZBEK PROSE: A CASE STUDY OF O‘TKIR HOSHIMOV, NODIR ESHONQUL, AND SHUKUR HAMRO’S WORKS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the influence of William Faulkner’s narrative techniques and thematic paradigms on contemporary Uzbek prose. Through a comparative literary analysis of selected works by O‘tkir Hoshimov, Nodir Eshonqul, and Shukur Hamro, the paper identifies traces of Faulknerian elements such as stream of consciousness, nonlinear storytelling, multiple narrators, and deep psychological introspection. The study situates these influences within the broader postmodern evolution of Uzbek fiction and discusses how local writers adapt global literary traditions to reflect national identity, historical trauma, and moral decay.